Psychological and linguistic features of the Russian language acquisition by international students - I A Novikova; A L Novikov; M A Rybakov (Peoples' Friendship University of Russia (RUDN University), 2015)
The paper presents the results of a full-scale interview with Russian language teachers that teach Russian as a foreign language at the preparatory departments at multinational universities. The research findings identified the basic psychological and linguistic features that are typical for the Russian language acquisition by the students from different regions of the world (Africa, Latin America, Southeast Asia, Arab countries).